Teachers' feedback in inclusive classrooms: A mixed method study - Arik Karamik, Gözdegül; Özkaya, Ali; Sönmez, Nesrin; Ayvalli, Merve (LPMPP Universitas Negeri Yogyakarta, 2026)
Feedback, which is important for every environment involving communication, plays a key role in solving the difficulties experienced by students, especially in learning environments. In this study, mixed method research was conducted to determine the awareness of mathematics and classroom teachers working in inclusive classrooms about giving feedback and how students with learning difficulties (LD) perceive their teachers' feedback. In the qualitative phase of the study, where an exploratory sequential design (sequential qualitative → quantitative) from mixed research methods was used, interviews were conducted with teachers and students, the data obtained from these interviews were analyzed and an item pool was created for the ‘Teachers' Feedback Awareness Scale in Inclusive Classrooms (TFASIC)’ by using the framework in the literature for feedback. In the quantitative phase of the study, the validity and reliability data of the scale were collected and analyzed. Qualitative data revealed that the feedback given by the teachers differed in terms of type, clarity, depth, focal point and mode of delivery. It was concluded that students with LD who evaluated teachers' feedback received feedback under these five headings. The TFASIC proved to be a measurement tool that produces valid and reliable results.